COLOR COMBINATION IN THE ART OF SPECIAL CHILDREN: A STUDY (WITH REFERENCE TO THE DEAF AND DUMB CHILDREN): विशेष बालकों की कला में रंग संयोजनः- एक अध्ययन (मूक-बधिर बालकों के विषेष सन्दर्भ मे) - Singh Naruka Phoolita, Yogendra (International Journal of Research -GRANTHAALAYAH, 2014)
Making art work with special children (mentally challenged, deaf, deaf, blind) is a challenging task in itself. Creating an understanding of colors in them, explaining their meaningful use and then moving them towards creativity is a laborious task. To understand the color combinations of special children, first of all they should be left alone to paint something with color, canvas and brushes. After some time their color combination should be visible. The special emotions and emotions of children can be understood by colors. Pride and happiness can be seen in children who use yellow and purple colors, while children who use red color more often show signs of rage and anger. Children who use green color are happy and anxious. Similarly, children who use blue more are of calm and stable nature. विषेष बालकों (मानसिक,विकलंाग,मूक-बधिर,अंध) से कला सृजनकार्य करवाना अपने आप में एक चुनौती पूर्ण कार्य है। उनमें रंगों की समझ पैदा करना, उनके सार्थक उपयोग को समझाना और फिर उसे सृजनात्मकता की ओर अग्रसर करना श्रम साध्य कार्य है। विषेष बालकों के रंग संयोजन को समझने के लिए सर्वप्रथम उन्हें रंग, कैनवास और ब्रष के साथ कुछ चित्रित करने के लिए अकेले छोड़ देना चाहिए। कुछ समय बाद उनके रंग-संयोजन को दृष्टिगत करना चाहिए। रंगों से विषेष बालकों की मानसिक भावनाओं और संवेगों को समझा जा सकता है। पीले व बैंगनी रंग का अधिक उपयोग करने वाले बालकों में प्रफुल्लता और खुषी के भाव देखे जा सकते है वहीं लाल रंग का अधिक प्रयोग करने वाले बालकों में उग्रता व क्रोध के लक्षण दिखाई देते है। हरे रंग का प्रयोग करने वाले बालक प्रसन्नता और निष्चिंता लिए होते है। इसी तरह नीले रंग का अधिक प्रयोग करने वाले बालक शान्त व स्थिर प्रकृति के होते है।